Allograft Injury Following Nandrolone and High‐Dose Dietary Supplements Use in a Liver Transplant Recipient: A Case Report - Mahnaz Sadat Hosseini; Simin Dashti‐Khavidaki; Monavar Talebian; Mohsen Nasiri‐Toosi; Masoomeh Safaei (Clinical Case Reports)
ABSTRACT This case report highlights the importance of meticulous monitoring of all medications and dietary supplements used by solid organ transplant recipients. Although the recommended daily allowances of vitamins, minerals, and herbs are generally considered safe, combining various supplement formulations can result in excessive intake, thereby increasing the risk of allograft injury in this patient population.